Strange times indeed: the evolving significance of myocardial ischaemia and the dwindling importance of functional imaging - Adrian Ionescu (Sciendo, 2021)
The ISCHEMIA trial is only the latest and most compelling link in a chain of evidence that suggests that myocardial ischaemia per se is not an appropriate treatment target for patients with stable coronary artery disease. This review is trying to make sense of the momentous and sometimes contradictory recent developments in the space of imaging for myocardial ischaemia.